2020
DOI: 10.1038/s41598-020-77003-3
|View full text |Cite
|
Sign up to set email alerts
|

High-content screening of Thai medicinal plants reveals Boesenbergia rotunda extract and its component Panduratin A as anti-SARS-CoV-2 agents

Abstract: Since December 2019, the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused severe pneumonia, a disease named COVID-19, that became pandemic and created an acute threat to public health. The effective therapeutics are in urgent need. Here, we developed a high-content screening for the antiviral candidates using fluorescence-based SARS-CoV-2 nucleoprotein detection in Vero E6 cells coupled with plaque reduction assay. Among 122 Thai natural products, we found that Boesenbergia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 61 publications
2
125
1
2
Order By: Relevance
“…The use of natural compounds from plants with proven activity against pathogenic viruses is one such strategy. Exploratory research of natural components that show anti-SARS-CoV-2 activity is being actively conducted and some candidate components have been reported by us and other groups in vitro [ 11 , 12 , 13 ]. Plant polyphenols are naturally-derived compounds that show antiviral activity against various pathogenic viruses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural compounds from plants with proven activity against pathogenic viruses is one such strategy. Exploratory research of natural components that show anti-SARS-CoV-2 activity is being actively conducted and some candidate components have been reported by us and other groups in vitro [ 11 , 12 , 13 ]. Plant polyphenols are naturally-derived compounds that show antiviral activity against various pathogenic viruses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products acting, for example, on such mechanisms exacerbated during COVID-19, such as pulmonary hypertension, notoriously borne by Glycyrrhiza glabra extracts, should be further examined in docking research to gather those compounds able to provide benefits in COVID-19 patients [ 16 ]. Important clinical trials are also planned to highlight which type of herbal extracts can address COVID-19 [ 17 , 18 ]. The issue of using folk medicine is fundamental for at least two reasons.…”
mentioning
confidence: 99%
“…Kanjanasirirat et al , [ 26 ] tested 122 Thai natural products and found panduratin A from Boesenbergia rotunda as potent anti-SARS-CoV-2 inhibitor. Treatment of Vero E6 cells with B. rotunda extract and panduratin An upon viral infection drastically suppressed SARS-CoV-2 infectivity with IC 50 values of 3.62 μg/mL (CC 50 = 28.06 μg/mL) and 0.81 μΜ (CC 50 = 14.71 μM), respectively.…”
Section: Resultsmentioning
confidence: 99%